Phylogeny and diversity of the morphologically similar polypore genera Rigidoporus, Physisporinus, Oxyporus, and Leucophellinus - Wu, Fang; Chen, Jia-Jia; Ji, Xiao-Hong; Vlasák, Josef; Dai, Yu-Cheng (Mycologia, 2017)
Rigidoporus and its morphologically similar genera Physisporinus, Oxyporus, and Leucophellinus, which include some forest pathogens and medicinal species, are very important groups of wood-decaying fungi. Species of these genera have not only ecological functions, but also economic importance. Phylogenetic and taxonomic studies on taxa in these genera were carried out. Inferred from phylogenies based on DNA sequences of the nuc rDNA ITS1-5.8S-ITS2 (internal transcribed spacer [ITS]) and D1-D2 domains of nuc 28S rDNA, 36 species sampled that traditionally belong to Physisporinus, Rigidoporus, Leucophellinus, and Oxyporus are nested mostly in eight lineages. Of these lineages, five (including four genera of Physisporinus, Emmia, Flaviporus, and Flavodon and one taxon "R. hypobrunneus") belong to Polyporales and three (including the genera Rigidoporus, Bridgeoporus, and Leucophellinus) belong to Hymenochaetales. Rigidoporus and Oxyporus are merged because the type species of both genera are nested in a single lineage within Hymenochaetales. Some taxon previously placed in Ceriporia and Oxyporus are transferred to Emmia and Flavodon, respectively, on the basis of current phylogeny. Utilizing a combination of the morphological and phylogenetic evidence, 16 new combinations in Bridgeoporus, Emmia, Flaviporus, Flavodon, Rigidoporus, and Physisporinus are proposed. Five new species, Physisporinus crataegi, P. lavendulus, P. subcrocatus, P. tibeticus, and Rigidoporus submicroporus, are recognized from China. Illustrated descriptions of these novel species are provided. Three taxa are treated at the generic level of Physisporinus because of limited samples.
Keywords: DNA fungální; mezerníky ribozomální DNA; DNA, Fungal; DNA, Ribosomal; Phylogeny; phylogenetic analysis; Sequence Analysis, DNA; Čína; Cluster Analysis; China; RNA, Ribosomal, 5.8S; sekvenční analýza DNA; Polyporales; fylogeneze; shluková analýza; ribozomální DNA; RNA ribozomální 5.8S; Basidiomycota; DNA, Ribosomal Spacer; Hymenochaetales; RNA, Ribosomal, 28S; RNA ribozomální 28S